2014
DOI: 10.1007/s10753-014-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Aspalathin and Nothofagin from Rooibos (Aspalathus linearis) Inhibits High Glucose-Induced Inflammation In Vitro and In Vivo

Abstract: Vascular inflammation plays a key role in the initiation and progression of atherosclerosis, a major complication of diabetes mellitus. Aspalathin (Asp) and nothofagin (Not) are two major active dihydrochalcones found in green rooibos, which have been reported for their antioxidant activity. In this study, we assessed whether Asp or Not can suppress vascular inflammation induced by high glucose (HG) in human umbilical vein endothelial cells (HUVECs) and mice. We monitored the effects of Asp or Not on HG-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 49 publications
0
26
2
Order By: Relevance
“…Demonstration of antidiabetic properties for aspalathin (Kawano et al, 2009;Muller et al, 2012;Son et al, 2013;Mazibuko et al, 2015), the major flavonoid and novel dihydrochalcone of green rooibos extracts with anti-diabetic activity (Kamakura et al, 2015;Muller et al, 2012), indicates its relevance as a critical quality parameter. Other compounds of importance in the same context are nothofagin, the 3-deoxy analogue of aspalathin, and the flavone derivatives of aspalathin, iso-orientin and orientin, by virtue of their relevant prominence in these extracts and their bioactivity (Sezik et al, 2005;Alonso-Castro et al, 2012;Annapurna et al, 2013;Mazibuko, 2014;Ku et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Demonstration of antidiabetic properties for aspalathin (Kawano et al, 2009;Muller et al, 2012;Son et al, 2013;Mazibuko et al, 2015), the major flavonoid and novel dihydrochalcone of green rooibos extracts with anti-diabetic activity (Kamakura et al, 2015;Muller et al, 2012), indicates its relevance as a critical quality parameter. Other compounds of importance in the same context are nothofagin, the 3-deoxy analogue of aspalathin, and the flavone derivatives of aspalathin, iso-orientin and orientin, by virtue of their relevant prominence in these extracts and their bioactivity (Sezik et al, 2005;Alonso-Castro et al, 2012;Annapurna et al, 2013;Mazibuko, 2014;Ku et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Plants derived polyphenols such as quercetagetin, fisetin, and quercetin, which belong to the flavonoid family, have been shown to be effective inhibitors of mammalian alpha-amylase with IC50s in the order of µM [1]. Aspalathin (Asp) is the major active dihydrochalcones found in green rooibos, which have been reported many interesting biological properties [12]. These include its antiinflammatory, antioxidant, antidiabetic, antihyperuricemic [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was important since experimental and clinical studies support the notion that drug compounds that enhance intracellular antioxidant properties can further exhibit a wide range of beneficial effects against the development of metabolic syndrome [29]. In addition to its robust antioxidant activity [28,[30][31][32][33][34], aspalathin can ameliorate inflammation [35][36][37][38][39], protect cardiac cells exposed to high glucose concentrations [40][41][42][43][44], and also display glucose lowering properties [45][46][47][48][49][50]. In addition to work by our group [46,48], studies conducted by Kawano et al [51] and Son et al [50] have reported on the effect of pure aspalathin or an aspalathin rich green rooibos extract on the signaling mechanisms that regulate glucose and lipid metabolism in skeletal muscle.…”
Section: Aspalathinmentioning
confidence: 99%